Housing Shortage in Soviet Russia in 1920s - Mikulenok, Julia Andreevna (Journal of History Culture and Art Research, 2018)
The following article examines a housing shortage on the threshold of revolution and during the first decade after establishment of the Soviet regime. Problems, which had been accumulating during the period before the revolution, escalated in 1920s. The first decade after the establishment of the Soviet government, the housing crisis reached its peak throughout the country. Looking for a way out of the current situation, the Soviet authorities carried out a whole range of measures, including “ushchemleniye former”, the transfer of the private housing fund to housing associations, condensation, control of housing construction and the differential distribution of square meters. But, they resulted in “housing wars”. The article deals with the housing policy of Soviet regime. The article is based on the background of the control authorities, publications and private sources.